PERANAN PENTINGNYA MENJAGA DAN MEMPERBAIKI KUALITAS UDARA DI INDONESIA - Abidin, Zaenal; Aldiyansyah; Sofyan, Alviansyah; Pratama Ginting, Alfrianto; Rosyani, Perani (BISIK : Jurnal Ilmu Komputer, Hukum, Kesehatan dan Sosial Humaniora, 2023)
Air quality plays a crucial role within the lifetime of living things on the surface, especially for humans, at this point the decline in air quality in several locations in Indonesia continues to extend because of several things including the expansion of industry and two-wheeled and four-wheeled vehicles which are increasing so rapidly. proportional to the increasing increment and not equivalent to the expansion of green open spaces and therefore the preservation of green areas, especially in urban areas. dust, smoke from industrial products, and oxygen levels within the air